Vulnerability in Children with Celiac Disease: A Scoping Review Protocol. - Macedo, Lúcia; Catarino, Marta; Festas, Constança; Alves, Paulo (Nursing Reports, 2022)
(1) Background: The scientific literature reports that children with celiac disease (CD) are more susceptible to developing physical, psychological and social problems, conditioning their healthy childhood development. Despite this scientific evidence, the knowledge about determinants of vulnerability for the development of such problems is not consistent. In order to search the literature, a scoping review was conducted to analyse and map the evidence on the sociopsychosomatic vulnerability of children with CD and identify the gaps in this topic. (2) Methods: The methodology proposed by the Joanna Briggs Institute will be adopted and aims to identify studies that meet pre-defined eligibility criteria. The survey will include a range of relevant electronic databases as well as grey literature using related terms such as vulnerability, child and celiac disease. (3) Results: This review will consider any type of quantitative, qualitative and mixed studies and systematic reviews, focusing on dimensions of vulnerability in children with CD. The process of selection of studies, data extraction and analysis will be developed by two independent researchers. A third and fourth researcher will be involved in the study when there is no consensus between the previous researchers, as well as for resolving issues regarding the methodological process. (4) Conclusions: Identifying the determinants of vulnerability in children with CD will help nurses to understand the impact on their childhood development and trace possible gaps. This research is registered on the platform Open Science Framework (OSF).